Dual Stator Permanent Magnet Vernier Machine With Yokeless Rotor Having Single Stator Winding for Torque Density Improvement - Mudassir Raza Siddiqi (IEEE, 2021)
This paper proposes a special design of a dual stator radial type permanent magnet vernier machine (PMVM) having a yokeless rotor to improve the torque density. The PMVM model is designed with winding only in the outer stator, while the inner stator is kept auxiliary without winding. The proposed model reduced the overall volume of the machine, which in turn improved the torque density of the machine. The proposed configuration makes the design free from thermal and manufacturing issues due to the absence of inner stator winding. The detailed specifications and analysis results of the proposed model, such as torque, back EMF, inductance, and other features, are presented in this paper. The model is analyzed and compared with the dual stator radial type PMVM having a yokeless rotor and dual stator winding using the 2D-Finite Element Method (FEM) as well as 3D Co-simulation with Ansys Mechanical.